Prevalência de Anticorpos Contra SARS-CoV-2 na População Residente no Município Português de Vila Nova de Gaia após a Primeira Onda da Pandemia - de Carvalho, Álvaro (2022)
Funding Information: This research was funded by Fundação Álvaro Carvalho (funding manager), Fundação Vox Populi, Fundação Manuel Viegas Guerreiro, and the Claude and Sofia Marion Foundation. The writing of the paper was also funded by the Fundação para a Ciência e a Tecnologia under the grants UIDB/04295/2020, UIDP/04295/2020, UIDB/04293/2020, and UIDP/04923/2020.